PELAKSANAAN PEMBELAJARAN SOSIOLOGI DENGAN PENDEKATAN DEEP LEARNING DALAM MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK DI KELAS X 3 SMAN 12 BUNGO - Ningsih, Indri Septi; Nurdin, Buchari; Sri Wahyuni, Yanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning activity of students in Sociology learning in class X 3 of SMAN 12 Bungo which is characterized by the lack of student participation in discussions, courage to express opinions, the ability to ask questions, and involvement in the learning process. The Deep Learning approach is seen as one of the learning alternatives that is able to create a meaningful learning process (meaningful learning), full of awareness (mindful learning), and joyful learning, so that it can increase the active involvement of students. This study aims to describe the implementation of Sociology learning with a Deep Learning approach which includes the planning, implementation, and evaluation stages, as well as identify the advantages and disadvantages of its application in increasing the learning activity of students in class X 3 SMAN 12 Bungo. The theory used in this study is Lev Vygotsky's Social Constructivism Theory as the main basis for analyzing the implementation of Sociology learning with a Deep Learning approach in increasing student activity. This study uses a qualitative approach with a descriptive research type. The research informants were selected using the purposive sampling technique consisting of Sociology teachers and 6 students of class X 3 of SMAN 12 Bungo. Data were collected through observations, in-depth interviews, and documentation studies. Furthermore, data analysis was carried out using the Miles and Huberman model which included data collection, data reduction, data presentation, as well as inference withdrawal and verification. The results of the research conducted in class X 3 of SMAN 12 Bungo show that the implementation of Sociology learning with the Deep Learning approach has been carried out through the stages of planning, implementation, and evaluation. In the planning stage, teachers develop learning tools that internalize the principles of meaningful learning, mindful learning, and joyful learning. The implementation places teachers as facilitators through discussions, analysis of social phenomena, presentations, and contextual learning, while the evaluation includes cognitive aspects and student activity. The application of the Deep Learning approach has been proven to increase students' activeness in visual, oral, listening, motor, mental, and emotional aspects. However, its implementation still faces obstacles in the form of limited facilities, time management, teacher readiness, and differences in student characteristics.